A Study on the Work Life Balance of Generation Y Information Technology (IT) Employees in Cochin - Kumar, Krishna; Velmurugan, R (International Journal of Engineering and Technology, 2018)
This research was performed to better understand the work life balance of Generation Y Information Technology Professionals in Cochin. Data were collected from a sample of 374 participants working in various Software Companies in Cochin using questionnaires, seeking information on socio economic background, job details, quality of work life, work life balance and job satisfaction. The study has helped people to a large extent in understanding the expectations of Generation Y IT employees from their organizations and how their socio economic background influences their work life balance.Â Â